Կարմրուկի, կարմրախտի տարածվածությունը և իմունականխարգելումը Հայաստանում - Հ. Ս. Հովհաննիսյան; Ն. Ս. Մելքոնյան (Հայաստանի ԳԱԱ)
Цель данного исследования заключается в оценке заболеваемости и иммунопрофилактики кори и краснухи в Армении. Результаты исследования показали, что в Армении эпидемиологический надзор за корью и краснухой значительно улучшился в период с 2005 по 2015 годы. В Армении в 2007 году была эффективно проведена кампания дополнительной массовой иммунизации против кори и краснухи, что привело к прерыванию эндемичной передачи. The objective of this research has been the evaluation of immunoprophylaxis and morbidity of measles, rubella in Armenia. The results of this research have shown а significant improvement of the epidemiological surveillance and the morbidity in particular for measles and rubella in Armenia during 2005-2015. Supplementary immunization activities of measles and rubella were conducted effectively in Armenia in 2007, contributing to the interruption of endemic transmission.
Keywords: Medicine; Epidemiology